«Jeg vil bli en å regne med» - Aage Aagesen (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract Young men’s desistance from gangs involved in crime is a pressing social issue in the Nordic countries. Drawing from a larger study comprising life story interviews with previously incarcerated men across different life stages, this article elaborates the narration of desistance among three young men who desisted from gang-related crime in their early twenties. By telling their stories of involvement in crime and their desistance process as career shift narratives, continuity in their »real me« is emphasised. Their stories make them come across as rational agents concerned with independence, ambition and a goal-oriented agency proving their capacity and willingness to take responsibility through hard work in the construction industry. This narrative identity can be understood as the young men’s ideals of masculinity, which intertwine their earlier values and previous experiences with a new maturity gained by social relations to role models in the labour market and significant others. In line with this, ideals of masculinity may be seen as a narrative resource which may shape and enhance possibilities for secondary and tertiary desistance in early adulthood.